PEMANFAATAN PEMBAYARAN DIGITAL PADA UMKM DI SAMOSIR - Anne Rumondang Malau; Frederick Saroha Silaban (LPPM Universitas Bina Bangsa, 2023)
The development of information and communication technology moves very quickly, the world has seen how advances in information and communication technology can change people and the world's economic order. In general, UMKM players in the Samosir district still use cash in transactions, so they do not provide payment options for visitors or tourists. Therefore, along with the development of digital payments, UMKM players must be able to have payment options through digital payment channels. The purpose of this community service is to help the community or UMKM players in Samosir Regency to be able to adapt to the digitalization era where transactions use digital transactions. Thus, payment transactions can be made more efficiently or affordably, financial inclusion in Indonesia can be accelerated, and UMKM players can become more sophisticated, all of which contribute to economic growth. Guidance and direction to become human resources who think innovatively and have a creative spirit are needed to become an important capital in facing competition